Analisis Penggunaan Media Pembelajaran untuk Meningkatkan Minat Belajar Siswa Kelas VII pada Mata Pelajaran PAI di MTsS An-Nur Hamparan Perak - Indah Novita Sari; Fitri Amaliyah Batubara (Journal on Education, 2023)
This istudy iaimsi to describei how the use of learning media to increase student interest in learning and describe the efforts and problems that occur in increasing student interest in learning. To achieve the goals of Islamic education, in the learning process the teacher should use learning media to make the learning process more interesting and easy for students to understand. Islamic Religious Education Learning Media is everything that can be used to convey materials and materials about Islam to students so that the Muslim personality is realized in accordance with the values ​​contained in Islam. The characteristics of Islamic learning media can be classified into graphic media, audio media and silent projection media. Islamic Religious Education (PAI) is an effort to prepare students to understand, believe, be pious, have noble character, and carry out Islamic religious teachingsi that have been taught from the main source, namely the holy book al-Quran and al-Hadith, through guidance, teaching activities. , training, iand iimplementing religiousi knowledge iin daily ilife. This istudy uses qualitativei methods with i field iresearch. iThe iresultsi of the study indicate that the success supporting factor to increase student interest in learning in the process of ilearning iactivities iis ithe use iof ilearning imedia.